Work Loss and Direct and Indirect Costs Associated with Parkinson’s Disease - Jerry M; Arcona S; McMorrow D; Schwartz H; Princic N; Sasane R (Dove Medical Press, 2023)
Michelle Jerry,1 Steve Arcona,2 Donna McMorrow,1 Hana Schwartz,1 Nicole Princic,1 Rahul Sasane2 1Merative, Ann Arbor, MI, USA; 2Cerevel Therapeutics, Cambridge, MA, USACorrespondence: Michelle Jerry, Merative, 100 Phoenix Dr Ste 200, Ann Arbor, MI, 48108, USA, Email michelle.jerry@merative.comPurpose: To examine work loss and indirect costs during the three-year periods prior to and following initial diagnosis of Parkinson's disease (PD) in patients and in spouses of PD patients, as well as direct costs of healthcare.Patients and Methods: This is a retrospective, observational cohort study using the MarketScan Commercial and Health and Productivity Management databases.Results: A total of 286 employed PD patients and 153 employed spouses met all diagnostic and enrollment criteria for short-term disability (STD) analysis (PD Patient cohort and Caregiving Spouse cohort). The proportion of PD patients having a STD claim increased from roughly 5% and plateaued at around 12- 14% starting in the year prior to first diagnosis of PD. The mean number of days lost from work due to STD per year increased from 1.4 days in the 3rd year prior to diagnosis to 8.6 days in the 3rd year after diagnosis (corresponding to an increase in indirect costs from $174 to $1104). STD use for spouses of patients with PD was lowest in the year after their spouses were diagnosed and then rose dramatically in the 2nd and 3rd years after the spouse's diagnosis. Total all-cause direct health-care costs increased during the years leading up to PD diagnosis and were highest in the years following diagnosis, with PD-related costs contributing ~20- 30% of the total.Conclusion: PD has both a significant direct and indirect financial burden on patients and their spouses when analyzed for 3 years before and after diagnosis.Keywords: caregiver burden, cost of illness, health expenditures, prodromal symptoms, retrospective studies, sick leave